2019
DOI: 10.7287/peerj.preprints.27630v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Combining UAV-based hyperspectral imagery and machine learning algorithms for soil moisture content monitoring

Abstract: X. 2019. Combining UAV-based hyperspectral imagery and machine learning algorithms for soil moisture content monitoring. PeerJ 7:e6926 https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This research underscores the utility of CNN-based spectral analysis for evaluating cold damage in corn seedlings, facilitating the selection of cold stress-resistant crop varieties. In [225], the authors outline a methodology for precise estimation of soil moisture content (SMC) in arid regions using UAV hyperspectral data. It combines optimal spectral indices and ground observations in a machine learning framework to achieve highly accurate SMC predictions.…”
Section: B Agriculture and Food Quality And Safetymentioning
confidence: 99%
“…This research underscores the utility of CNN-based spectral analysis for evaluating cold damage in corn seedlings, facilitating the selection of cold stress-resistant crop varieties. In [225], the authors outline a methodology for precise estimation of soil moisture content (SMC) in arid regions using UAV hyperspectral data. It combines optimal spectral indices and ground observations in a machine learning framework to achieve highly accurate SMC predictions.…”
Section: B Agriculture and Food Quality And Safetymentioning
confidence: 99%
“…Due to the high degree of complexity between remote sensor data and soil characteristics, most work in this area has been assisted by machine learning approaches. Some research has utilized only remote sensing data analyzed with machine learning (Ge et al., 2019) to obtain estimates such as soil moisture. Generally, studies have combined remote sensing data with data including terrain models, electrical conductivity maps (Wijewardane et al., 2019), crop heights, crop temperatures (Hu et al., 2019), soil temperatures (Aboutalebi, Allen, Torres‐Rua, McKee, & Coopmans, 2019), and water holding capacities (Hassan‐Esfahani, Torres‐Rua, Jensen, & McKee, 2015) aided by machine learning to produce UAV‐derived soil organic carbon, salinity, and moisture maps, respectively.…”
Section: Uav Applications In Agriculturementioning
confidence: 99%
“…Compared with other spectral indices such as the normalized difference index and the ratio index, Ge et al. (2019) found that the two‐dimensional perpendicular index had the highest correlation with SMC. However, these spectral indices used only several bands and possibly neglected some other important spectral information that might decrease the prediction accuracy.…”
Section: Introductionmentioning
confidence: 99%